PENGENALAN KONSEP BILANGAN MELALUI ALAT PERMAINAN TRADISIONAL DAKON PADA ANAK USIA 5-6 TAHUN - Mega Fitri Lisjayanti; Ismatul Khasanah; Ellya Rakhmawati (Wawasan Pendidikan, 2022)
ABSTRACTThe introduction of the concept of numbers is very important to do in early childhood because the concept of numbers is included in cognitive development which is very important needed to support further education. To stimulate cognitive development, especially in the introduction of the concept of numbers, one way is to use traditional dakon game tools. Dakon game tools are one of the traditional tools that can stimulate the development of the concept of numbers in early childhood. The dakon game tool can only be played with two people, the introduction of the concept of numbers in the dakon is by using the dakon seeds, namely counting the dakon seeds and entering the dakon seeds in the dakon barn. The purpose of this paper is to explain the importance of recognizing the concept of numbers using traditional dakon game tools. This writing method uses a literature review method from several relevant article references. The results of this analysis indicate that traditional dakon game tools can stimulate several aspects of development, namely aspects of cognitive, physical, motor and social emotional development.